Perceptions among local community on conservation of Non-Timber Forest Products (NTFPs) in Cameron Highlands, Pahang - Mohd, Nur Akma Syahirah (2019)
Non-timber forest products (NTFP) represent vital sources of cash and subsistence income for millions of rural and indigenous peoples living in tropical developing countries throughout the world. The objectives of this study were to determine perceptions of the local community on the environmental issue affecting the sustainability of the NTFPs and to identify the socio-demographic factors causing differences in the opinion on appropriate conservation measures that can be used to protect the viability of NTFPs in this area. The questionnaire survey was conducted to obtain the required information and to fulfil the objectives of the study. A total of 111 respondents were interviewed. The result show most of the respondents agree that NTFPs is slowly to decrease and they also decided that conservation measures need to take action. This study indicates that socio-demographic factors were influencing the perception of respondents. In overall, respondents agreed that forest clearing for the several factors gives negative impacts to the production of NTFPs.